2012
DOI: 10.1051/0004-6361/201118151
|View full text |Cite
|
Sign up to set email alerts
|

Seismic modelling of the late Be stars HD 181231 and HD 175869 observed with CoRoT: a laboratory for mixing processes

Abstract: Context. HD 181231 and HD 175869 are two late rapidly rotating Be stars, which have been observed using high-precision photometry with the CoRoT satellite during about five consecutive months and 27 consecutive days, respectively. An analysis of their light curves, by Neiner and collaborators and Gutiérrez-Soto and collaborators respectively, showed that several independent pulsation g-modes are present in these stars. Fundamental parameters have also been determined by these authors using spectroscopy. Aims. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 66 publications
5
40
0
Order By: Relevance
“…Aerts (2015) presents 16 OB dwarfs for which asteroseismic determinations of the extent of overshooting have been made. Similar analyses have also been carried out by Neiner et al (2012) and Tkachenko et al (2014).…”
Section: Introductionsupporting
confidence: 55%
“…Aerts (2015) presents 16 OB dwarfs for which asteroseismic determinations of the extent of overshooting have been made. Similar analyses have also been carried out by Neiner et al (2012) and Tkachenko et al (2014).…”
Section: Introductionsupporting
confidence: 55%
“…Sharp variations in the mean molecular weight profile at the boundary of the mixed core create a glitch to which oscillation modes are sensitive, which can be used to measure the extent of the mixed region associated to convective cores. This approach has been successfully applied to solar-like pulsators in the main sequence (Deheuvels et al 2010b;Goupil et al 2011;Silva Aguirre et al 2013;Guenther et al 2014;Appourchaux et al 2015), in the subgiant phase (Deheuvels & Michel 2010, and to several main-sequence B stars (e.g., Degroote et al 2010;Neiner et al 2012;Moravveji et al 2015). All these studies report the need for extended convective cores and confirmed the great potential of asteroseismology to measure this extension.…”
Section: Introductionmentioning
confidence: 78%
“…In fact, non-axisymmetric nonradial oscillation modes work to transfer angular momentum in a star from the region where the oscillations are excited to other regions where dissipation works to damp the oscillations. As for Be stars, some attempts were made to see whether the nonradial g-modes efficiently work to accelerate the stellar surface rotation up to the break-up velocity (Ando 1983(Ando , 1986Osaki 1986Osaki , 1999Lee & Saio 1993;Lee 2008Lee , 2013Cranmer 2009;Neiner 2013). However, as far as we accept the aforementioned observational fact, we think that it is beside the point to consider the case that the stars rotate at the break-up limit.…”
Section: Mystery Of Angular Momentum Transfermentioning
confidence: 99%